EVALUATION OF RESPONSES AND STEPS TAKEN BY PARENTS TOWARDS THEIR CHILDREN WHO EXPERIENCE VISION IMPAIRMENT AFTER 2 YEARS OF ONLINE SCHOOLING - ulfiah zukhro sehe; Miftahul Akhyar Latief (RS Mata Makassar, 2024)
Background : The Covid-19 pandemic has had a major impact on education levels, resulting in learning that was initially carried out face-to-face changing to an online learning system. This online learning system is also supported by WHO so that the government gives instructions to stop all forms of activities that can cause crowds by doing all activities online.Objective : This study aims to analyze the relationship between parental responses to visual impairment in children after online learning during the COVID-19 pandemic. Method : The research method used is a prospective study. The sampling method is by using simple random sampling. The data collection method is by distributing questionnaires and data from the results of visual acuity examinations in grades 5 and 6. Sample : This study uses primary data from the results of questionnaire collection. Results : From the statistical test, the result was 0.134 (> 0.05), meaning that visual acuity disorders did not provide a response and steps for parents whose children experienced visual acuity disorders after online school for 2 years. Conclusion : The results of the study showed that there was no significant relationship between the steps taken by parents and the condition of children's vision.